Practicum Experiences of Prospective Teachers in Differentiating Instruction - Joseph, Stephen; John, Yvonne (Advances in Social Sciences Research Journal, 2014)
This study examined the experiences of prospective teachers in differentiating instruction during a two-week practicum assignment in an inclusive environment. Several school types were used ranging from denominational and government-led primary schools with students of low socio-economic status, to special schools for the physically handicapped and deaf students. The study employed a mixed-method research design aimed at triangulating quantitative and qualitative data obtained from questionnaires, focus group discussions, field notes from classroom observations, and student reflections. The total population comprised twenty-two year three students pursuing a Bachelor of Education degree in Special Needs Education; two practicum advisors; and nine cooperating teachers. Findings of the study revealed that prospective teachers achieved a measure of success in implementing differentiated instruction in their practicum classrooms. However, some attention should be given to cooperating teachers who may not provide the support expected of a mentor or coach due to a general lack of understanding of the philosophy of differentiated instruction. Keywords: practicum experiences, prospective teachers, differentiated instruction